2017
DOI: 10.1039/c6ra27426a
|View full text |Cite
|
Sign up to set email alerts
|

Electric field assisted growth and field emission properties of thermally oxidized CuO nanowires

Abstract: The growth and field emission properties of thermally oxidized CuO nanowires are influenced by the electric field intensity and direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 35 publications
1
18
0
2
Order By: Relevance
“…To meet this demand, a wide variety of metal oxide semiconductor nanostructures have been studied including ZnS, TiO 2 , CuO, SnO 2 , etc. [11][12][13] Among these materials, Silicon carbide (SiC) as a significant third-generation semiconductor material, with wide band gap (2.2-3.3 eV), mechanical stabilities, high thermal stability, high electrical and thermal conductivities, which is considered as one of the most promising materials for the potential application in the field of field emission devices. 14 Previously, in depth investigations into the growth of various SiC nanostructure morphology and tailoring the bandage to lower the field emission properties have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…To meet this demand, a wide variety of metal oxide semiconductor nanostructures have been studied including ZnS, TiO 2 , CuO, SnO 2 , etc. [11][12][13] Among these materials, Silicon carbide (SiC) as a significant third-generation semiconductor material, with wide band gap (2.2-3.3 eV), mechanical stabilities, high thermal stability, high electrical and thermal conductivities, which is considered as one of the most promising materials for the potential application in the field of field emission devices. 14 Previously, in depth investigations into the growth of various SiC nanostructure morphology and tailoring the bandage to lower the field emission properties have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…The results clearly demonstrated that the eld emission property of vertical Si nanowires was greatly enhanced aer the multiple ACER cycle process, mainly due to the formation of sharp-tip structures. Compared with previously reported data, the turn-on eld value of the periodic arrays of vertical tapered Si nanowires aer the 4 th ACER cycle (1.3 V mm À1 ) obtained in this study is much lower than that of most Si-based nanostructures (2.1-16.5 V mm À1 ), [3][4][5][6][7][8][9][10][30][31][32][33][34][35] and other semiconductor nanostructures, such as CuO nanowires (5.3-8.6 V mm À1 ), 36,37 ZnO nanopencils (3.2-3.7 V mm À1 ), 38,39 and GaN nanoneedles (3.5-9.0 V mm À1 ). 40,41 However, it should be noted from Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Results on the synthesis of Cu nanowires under a STM tip 24 and on CuO nanowires 25 by heating Cu foils at 400 C on a hotplate indicated that the process is favored by the application of an external electric eld, which promotes the diffusion/electromigration of Cu ions. 25 In the case of Mo, a thermal assisted electromigration process would enhance the out diffusion of Mo ions in the metal wire leading to the rapid growth of MoO 3 plates. Under electric eld a higher MoO 3 synthesis yield is observed with formation of the structures at lower temperatures than in absence of electric eld and in a faster process with times down to few seconds.…”
Section: Structures Formed On the Mo Wirementioning
confidence: 99%